National Performance on the Medicare SEP-1 Sepsis Quality Measure. Issue 8 (August 2019) - Barbash, Ian J.; Davis, Billie; Kahn, Jeremy M.
Abstract : Objectives: The Centers for Medicare and Medicaid Services requires hospitals to report compliance with a sepsis treatment bundle as part of its Inpatient Quality Reporting Program. We used recently released data from this program to characterize national performance on the sepsis measure, known as SEP-1. Design: Cross-sectional study of United States hospitals participating in the Centers for Medicare and Medicaid Services Hospital Inpatient Quality Reporting Program linked to Centers for Medicare and Medicaid Services' Healthcare Cost Reporting Information System. Setting: General, short-stay, acute-care hospitals in the United States. Measurements and Main Results: We examined the hospital factors associated with reporting SEP-1 data, the hospital factors associated with performance on the SEP-1 measure, and the relationship between SEP-1 performance and performance on other quality measures related to time-sensitive medical conditions. A total of 3, 283 hospitals were eligible for the analysis, of which 2, 851 (86.8%) reported SEP-1 performance data. SEP-1 reporting was more common in larger, nonprofit hospitals. The most common reason for nonreporting was an inadequate case volume. Among hospitals reporting SEP-1 performance data, overall bundle compliance was generally low, but it varied widely across hospitals (mean and SD: 48.9% ± 19.4%). Compared with hospitals with worse SEP-1 performance, hospitals with better SEP-1 performance tended to be smaller, for-profit, nonteaching, and with intermediate-sized ICUs. Better hospital performance on SEP-1 was associated with higher rates of timely head CT interpretation for stroke patients (rho = 0.16; p < 0.001), more frequent aspirin administration for patients with chest pain or heart attacks (rho = 0.24; p < 0.001) and shorter median time to electrocardiogram for patients with chest pain (rho = –0.12; p < 0.001). Conclusions: The majority of eligible hospitals reported SEP-1 data, and overall bundle compliance was highly variable. SEP-1 performance was associated with structural hospital characteristics and performance on other measures of hospital quality, providing preliminary support for SEP-1 performance as a marker of timely hospital sepsis care.